Study of Pd-based catalysts within red algae-derived polysaccharide supports in a Suzuki cross-coupling reaction. Issue 66 (12th November 2018) - Wolfson, Adi; Biton, Shira; Levy-Ontman, Oshrat
Abstract : Simple palladium complexes were heterogenized into red algae derived polysaccharide supports, and the effects of polysaccharide, catalyst and solvent types on the performances in a Suzuki cross-coupling reaction were tested. Abstract : Simple palladium complexes were heterogenized into red algae derived polysaccharide supports, and the effects of polysaccharide, catalyst and solvent types on the performances in a Suzuki cross-coupling reaction were tested. It was found that using palladium salts with sodium triphenylphosphine trisulfonate (TPPTS) as a ligand supported on ι-carrageenans and ethanol as the solvent yielded the best systems. Moreover, the conversion rates of these heterogeneous systems were higher than their homogeneous analogues, and they were easily recycled five times. SEM-EDS analysis of Pd(OAc)2 (TPPTS)2 that was immobilized on ι-carrageenan support was also performed, demonstrating that the system has a porous structure composed of Pd complex that was embedded within the ι-carrageenan. In addition, both ι-Pd(OAc)2 (TPPTS)2 and ι-Pd(OAc)2 systems, were composed of nanoparticles, as proven by TEM analysis.